Association of cardiac calcium burden with overall survival after radiotherapy for non-small cell lung cancer. (January 2023) - Haseltine, Justin M.; Apte, Aditya; Jackson, Andrew; Yorke, Ellen; Yu, Anthony F.; Plodkowski, Andrew; Wu, Abraham; Peleg, Ariel; Al-Sadawi, Mohammed; Iocolano, Michelle; Gelblum, Daphna; Shaverdian, Narek; et al.
Abstract: Background and purpose: Coronary calcifications are associated with coronary artery disease in patients undergoing radiotherapy (RT) for non-small cell lung cancer (NSCLC). We quantified calcifications in the coronary arteries and aorta and investigated their relationship with overall survival (OS) in patients treated with definitive RT (Def-RT) or post-operative RT (PORT). Materials and methods: We analyzed 263 NSCLC patients treated from 2004 to 2017. Calcium burden was ascertained with a Hounsfield unit (HU) cutoff of > 130 in addition to a deep learning (DL) plaque estimator. The HU cutoff volumes were defined for coronary arteries (PlaqueCoro ) and coronary arteries and aorta combined (PlaqueCoro+Ao ), while the DL estimator ranged from 0 (no plaque) to 3 (high plaque). Patient and treatment characteristics were explored for association with OS. Results: The median PlaqueCoro and PlaqueCoro+Ao was 0.75 cm 3 and 0.87 cm 3 in the Def-RT group and 0.03 cm 3 and 0.52 cm 3 in the PORT group. The median DL estimator was 2 in both cohorts. In Def-RT, large PlaqueCoro (HR:1.11 (95%CI:1.04–1.19); p = 0.008), and PlaqueCoro+Ao (HR:1.06 (95%CI:1.02–1.11); p = 0.03), and poor Karnofsky Performance Status (HR: 0.97 (95%CI: 0.94–0.99); p = 0.03) were associated with worse OS. No relationship was identified between the plaque volumes and OS in PORT, or between the DL plaque estimator and OS in either Def-RT or PORT. Conclusions: Coronary artery calcification assessed from RT planning CT scans was significantly associated with OS in patients who underwent Def-RT for NSCLC. This HU thresholding method can be straightforwardly implemented such that the role of calcifications can be further explored.